Oxidative Cyclization Reactions: Controlling the Course of a Radical Cation‐Derived Reaction with the Use of a Second Nucleophile1. Issue 49 (19th November 2013) - Redden, Alison; Perkins, Robert J.; Moeller, Kevin D.
<x xml:space="preserve">Abstract</x> Construction of new ring systems: Oxidative cyclizations (see picture; RVC=reticulated vitreous carbon) have been conducted that use two separate intramolecular nucleophiles to trap an enol ether‐derived radical cation intermediate. The reactions provide a means for rapidly trapping the radical cation intermediate in a manner that avoids competitive decomposition reactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>